2021
DOI: 10.1155/2021/5807056
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Waves during the COVID-19 Pandemic: Retrospective Descriptive Study in Thailand

Abstract: Background. Coronavirus disease (COVID-19) is an infectious disease caused by a newly discovered coronavirus. An outbreak is called an epidemic when there is a sudden increase in cases. Many countries have experienced a two-wave pattern in the reported cases of COVID-19. The spread of COVID-19 in Thailand was a cluster event distributed over multiple locations. This study aims to compare the characteristics of different waves during the COVID-19 pandemic in Thailand. Methods. A retrospective cohort study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 30 publications
0
41
1
Order By: Relevance
“…Although there was a significant impact of developed vaccinations, the third wave further exposed varying social and financial differences in different countries [ 37 ]. Several studies focused on the characteristics of effects of viral disease in different seasons [ 38 , 39 , 40 , 41 ], but no study highlighted changes in perceiving fears of COVID-19 infection during different waves. For instance, Iftimie et al reported differences in age range and severity of the disease between two periods of COVID-19 infection (March–June 2020 and July–October 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although there was a significant impact of developed vaccinations, the third wave further exposed varying social and financial differences in different countries [ 37 ]. Several studies focused on the characteristics of effects of viral disease in different seasons [ 38 , 39 , 40 , 41 ], but no study highlighted changes in perceiving fears of COVID-19 infection during different waves. For instance, Iftimie et al reported differences in age range and severity of the disease between two periods of COVID-19 infection (March–June 2020 and July–October 2020).…”
Section: Discussionmentioning
confidence: 99%
“…All three studies were conducted in the first half of 2020 during the first wave of the pandemic, so they might be more comparable in terms of virus variants and the impact of a specific wave, since the different waves and variants of the virus had varying impacts on the world population and its health [23,24]. An important aspect of a study is choosing a representative group of participants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the handful of P. vivax and COVID-19 co-infections reported seems to suggest it is a relatively uncommon event. In Thailand, strict public health measures and very limited international travel bans were implemented in March 2020, keeping COVID-19 cases to a minimum, with approximately only 4000 COVID-19 infections countrywide from March to November 2020 [ 24 ]. As the country began to open to travelers, larger waves then began to occur.…”
Section: Discussionmentioning
confidence: 99%